High Frequency of Fibromyalgia in Patients With Acne Vulgaris - Levent YAZMALAR,; Tahsin ÇELEPKOLU,; İbrahim BATMAZ,; Mustafa Akif SARIYILDIZ,; Bilal SULA,; Mahmut ALPAYCI,; İsa AN,; Yahya Kemal BURKAN,; Haydar UÇAK,; Remzi ÇEVİK, (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the frequency of fibromyalgia syndrome and to specify fibromyalgia syndrome-associated clinical symptoms in patients with acne vulgaris. Patients and methods: Eighty-eight patients (28 males, 60 females; mean age 23.2±5.1 years; range 18 to 40 years) with acne vulgaris and age, sex- and body mass index-similar 76 healthy controls (14 males, 62 females; mean age 24.5±2.9 years; range 18 to 35 years) were included. Acne vulgaris was evaluated by using the Global Acne Scale, while Hospital Anxiety and Depression Scale was used to evaluate anxiety. Results: Fibromyalgia-associated pain, sleep disturbance, anxiety, and menstrual cycle disturbance were significantly more frequent in patients with acne vulgaris than controls. Also, the severity of anxiety and the number of tender points were significantly higher in the acne vulgaris patients than controls. Conclusion: This study indicates that patients with acne vulgaris have increased frequency of fibromyalgia syndrome than healthy controls (21.6% versus 5.3%, respectively).